2021
DOI: 10.1101/2021.01.19.427347
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LINE-1 Retrotransposon expression in cancerous, epithelial and neuronal cells revealed by 5’ single-cell RNA-Seq

Abstract: LINE-1 retrotransposons are known to be expressed in early development, in tumors and in the germline. Less is known about LINE-1 expression at the single cell level, especially outside the context of cancer. Because LINE-1 elements are present at a high copy number, many transcripts that are not driven by the LINE-1 promoter nevertheless terminate at the LINE-1 3’ UTR. Thus, 3’ targeted single cell RNA-seq datasets are not appropriate for studying LINE-1. However, 5’ targeted single cell datasets provide an o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 79 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…Activity of LINE-1 has been recorded during early stages of development, in some specific cellular contexts such as oocyte attrition or neurogenesis, and under stress conditions such as aging and pathological conditions including cancer [11][12][13][14][15]. Recent experiments suggest activity of LINE-1 elements in epithelial cells [16]. In vitro experiments have shown that, in conditions of high LINE-1 derepression and expression, the machinery that mediates LINE-1 retrotransposition, can mobilize other sequences such as Alu and SVA elements, and can even lead to integration of certain cellular mRNAs, leading to the formation of processed pseudogenes [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Activity of LINE-1 has been recorded during early stages of development, in some specific cellular contexts such as oocyte attrition or neurogenesis, and under stress conditions such as aging and pathological conditions including cancer [11][12][13][14][15]. Recent experiments suggest activity of LINE-1 elements in epithelial cells [16]. In vitro experiments have shown that, in conditions of high LINE-1 derepression and expression, the machinery that mediates LINE-1 retrotransposition, can mobilize other sequences such as Alu and SVA elements, and can even lead to integration of certain cellular mRNAs, leading to the formation of processed pseudogenes [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrate that ORF1p is an early indicator of chemotherapeutic response in gastric and esophageal cancers at timepoints where other parameters are often ambiguous, opening possibilities for monitoring minimal residual disease or relapse. Importantly, ORF1p appears to provide a level of specificity for cancers not achieved by other protein biomarkers, likely due to the unique biology of the retrotransposon, with repression of L1 in normal somatic tissue(9,13,14). ORF1p is therefore attractive as a putative “binary” cancer biomarker, in which a positive signal is highly specific for disease, with diagnostic utility both in tissue and plasma.…”
Section: Discussionmentioning
confidence: 99%
“…We each inherit, dispersed throughout our genomes, a complement of active L1 loci encoding two proteins: ORF1p, the highly expressed RNA binding protein(8), and ORF2p, an endonuclease and reverse transcriptase with limited expression(9) that generates L1 insertions in cancer genomes(1013). L1 expression is repressed in normal somatic tissues, resulting in either very low or undetectable levels of L1 RNA and protein that appear to originate from epithelium(9,14). Epigenetic dysregulation of L1 and L1 ORF1p overexpression begin early in carcinogenesis, and histologic precursors of ovarian, esophageal, colorectal, and pancreatic cancers studied all express ORF1p at varying levels(8,15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation